My itineraries and experiences in the biographical and narrative universe: between desire and reality - González-Monteagudo, José (Adult Education Discourses, 2024)
In this text, which attempts to relate my professional history, my international experiences and my written contributions in recent years, I present my itinerary as a researcher and educator in the biographical-narrative field over the last two decades. This contribution addresses, from a personal and subjective point of view, the recent changes in the biographical universe referred to globalisation, teamwork, international collaboration, the creation of networks and the progressive consolidation, legitimisation and maturation of narrative approaches. I refer to the French-speaking model of the Histoires de Vie en Formation, as a social, epistemological and methodological proposal that seems to me essential to further deepen the biographical in educational contexts. I also characterise some important paradigms of social and educational research, which are of great relevance for the further construction of the biographical-narrative field. I conclude the text with some comments on current challenges and emerging issues in the biographical field.